Developing Indicators of Learning Organization of Phrapariyattidhamma School, Division of General Education in Thailand - Sricharumedhiyan, Phrakhruwinaithorn Chakkree; Kosolkittiamporn, Soawalak; Phosing, Pakdee (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
The purposes of this research were 1) to create indicators of learning organization of Phrapariyattidhamma School, a division of general education, in Thailand, 2) to develop indicators of learning organization of Phrapariyattidhamma School, a division of general education in Thailand, and 3) to investigate its consistency of structural relationship model of indicators of learning organization of Phrapariyattidhamma School, a division of general education in Thailand based on empirical data. In this research, questionnaires on 5 levels of rating, reliability at 0.980 and content validity at 0.60 – 1.00 were done and data were analyzed by a computer package for data analysis and M-Plus was used to analyze confirmatory factor. The research findings were found as follows: 1. The result concerning the creation of conceptual frameworks and development of indicators of learning organization of Phrapariyattidhamma School, a division of general education in Thailand was of 5 factors: 1) organization, 2) leadership, 3) learning, 4) knowledge management, and 5) information technology. 2. The results of the development of the indicators of learning organization of Phrapariyattidhamma School, a division of general education in Thailand. From the synthesis of the expert group discussions to determine the indicator found that draft indicators majority met for the purpose of research and appropriate. The details of the indicators that have been synthesized from the discussion groups of 82 indicators. 3. With respect to the result of investigation of consistency on the structural relationship model of indicators of learning organization of Phrapariyattidhamma School, a division of general education in Thailand, it was found that such a model was in consistent with empirical data (Chi – square) at 14932.208 with, degree of freedom at 3217, probability value (P-value) at 0.0000, comparative fit index (CFI) at 0.979, Trucker Lewis Index (TLI) at 0.975, Standard Root Mean Square Residual (SRMR) at 0.048, Root Mean Square Error of Approximation (RMSEA) at 0.000.